The Effect of NLRP3 Inflammasome on Wound Healing - Nur Aliviya Ananda; Reeny Purnamasari Juhamran (SEAN Institute, 2026)
Wound healing is a complex biological process involving hemostasis, inflammation, proliferation, and remodeling. One of the key regulators of the inflammatory phase is the NLRP3 inflammasome, a multiprotein complex that plays a role in the activation of caspase-1 and the release of the proinflammatory cytokine interleukin-1.β(IL-1β) and interleukin-18 (IL-18), as well as the induction of pyroptosis. Physiological activation of NLRP3 is required to initiate an immune response, but excessive activation can prolong inflammation and inhibit the wound healing process. Therefore, studying the effect of the NLRP3 inflammasome on wound healing is important as a basis for developing inflammation-modulating therapies. This study used a literature review method by examining 25 scientific articles published in 2022–2026. The literature search was conducted through the PubMed, Google Scholar, ScienceDirect, SpringerLink, Frontiers, Nature Publishing Group, and MDPI databases using keywords related to NLRP3 inflammasome, wound healing, pyroptosis, diabetic wound, and inflammation. Data were analyzed descriptively narratively to identify the mechanism of NLRP3 activation, its role in wound healing, and potential therapies targeting this pathway. The results of the synthesis indicate that the NLRP3 inflammasome plays a crucial role in regulating the inflammatory response during wound healing. Inflammasome activation is required in the early phase for pathogen elimination and clearance of damaged tissue, but excessive activation increases IL-1 production.β, IL-18, and pyroptosis, thereby inhibiting angiogenesis, fibroblast proliferation, collagen deposition, and re-epithelialization. Various studies have shown that modulating NLRP3 using probiotics, natural compounds, hydrogels, stem cell-derived extracellular vesicles, and exosomes can suppress inflammation, enhance tissue regeneration, and accelerate wound healing, especially in diabetic wounds, burns, and radiation injuries. The NLRP3 inflammasome has a dual role in wound healing: it acts as a key regulator of the inflammatory response and as a factor that can inhibit tissue regeneration if overactivated. Modulating NLRP3 activity is a promising therapeutic strategy to accelerate wound healing by controlling inflammation and enhancing tissue regeneration.